Peran Roh Kudus dalam Pendidikan Agama Kristen di Keluarga - Chanita Christie; Christofer Cahyadi; Djuwansah Suhendro P Stephanus; Lia Lesty S; Lidiawati Lidiawati (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2024)
This article discusses the role of the Holy Spirit in Christian Religious Education within the family in the digital era. Modern parents face new challenges posed by technological advancements, such as excessive screen time and the negative impacts of digital media. Therefore, they need to integrate spiritual guidance with digital literacy and technological skills, relying on the Holy Spirit for wisdom and understanding in teaching Christian values. The Holy Spirit plays a role in helping parents educate their children in the truth and Christian values, as well as teaching online ethics, internet safety, and wise technology use. Through a balanced and wise approach, and with the support of the Holy Spirit, parents can guide their children to become intelligent, responsible individuals who are prepared to face an ever-changing future. The Holy Spirit also assists parents in creating a family environment that is loving, peaceful, and harmonious, ideal for spiritual growth and character development. In this digital era, it is important for parents to utilize both spiritual and technological resources simultaneously to ensure the holistic well-being of their children, physically, mentally, and spiritually.